2017
DOI: 10.3390/ijms18020354
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Inflammation, Coagulation and Endothelial Injury in the Early Phase of Acute Pancreatitis: Clinical Implications

Abstract: Acute pancreatitis (AP) is an inflammatory disease with varied severity, ranging from mild local inflammation to severe systemic involvement resulting in substantial mortality. Early pathologic events in AP, both local and systemic, are associated with vascular derangements, including endothelial activation and injury, dysregulation of vasomotor tone, increased vascular permeability, increased leukocyte migration to tissues, and activation of coagulation. The purpose of the review was to summarize current evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
113
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 191 publications
(261 reference statements)
2
113
0
18
Order By: Relevance
“…Although the role of coagulation dysfunction in SAP pathogenesis has not been well understood, it is known that coagulation dysfunction is one of the common complications in SAP. Emerging evidence showed that coagulation dysfunction and inflammation could promote progression of SAP . Proinflammatory cytokines, particularly interleukin‐6, together with impaired endothelial cells could activate the coagulation process in local or systemic inflammatory state, inducing a hypercoagulable state .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of coagulation dysfunction in SAP pathogenesis has not been well understood, it is known that coagulation dysfunction is one of the common complications in SAP. Emerging evidence showed that coagulation dysfunction and inflammation could promote progression of SAP . Proinflammatory cytokines, particularly interleukin‐6, together with impaired endothelial cells could activate the coagulation process in local or systemic inflammatory state, inducing a hypercoagulable state .…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis, since the mean length of hospital stay were shorter in both 7-day and 14-day LMWH treatment subgroups than those of the conventional treatment subgroups, 7-day LMWH treatment is recommended because of an reduced risk of bleeding, while the course of treatment could be prolonged to 14 days when the SAP patients have high risk of embolization.Although the role of coagulation dysfunction in SAP pathogenesis has not been well understood, it is known that coagulation dysfunction is one of the common complications in SAP. Emerging evidence showed that coagulation dysfunction and inflammation could promote progression of SAP 31. Proinflammatory cytokines, particularly interleukin-6, together with impaired endothelial cells could activate F I G U R E 5 Forest plot of meta-analyses of A, acute physiology and chronic health evaluation (APACHE) II score and B, computed tomography severity index in low molecular weight heparin treatment group and conventional treatment group.…”
mentioning
confidence: 99%
“…An ideal prognostic marker is needed to show the severity of the disease in the early period and as a guide to treatment. Studies have suggested that parameters associated with coagulation disorder and inflammation, thought to play a significant role in the pathogenesis of the disease, can be used for his purpose [10, 18-20, 30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Coagulation disorders may develop in association with the severity of AP [6-10]. However, the pathogenesis of coagulation disorder in patients with AP is uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation